Biofilm formation on titanium implants counteracted by grafting gallium and silver ions. Issue 3 (18th July 2014) - Cochis, Andrea; Azzimonti, Barbara; Della Valle, Cinzia; Chiesa, Roberto; Arciola, Carla Renata; Rimondini, Lia
Abstract Biofilm‐associated infections remain the leading cause of implant failure. Thanks to its established biocompatibility and biomechanical properties, titanium has become one of the most widely used materials for bone implants. Engineered surface modifications of titanium able to thwart biofilm formation while endowing a safe anchorage to eukaryotic cells are being progressively developed. Here surfaces of disks of commercial grade 2 titanium for bone implant were grafted with gallium and silver ions by anodic spark deposition. Scanning electron microscopy of the surface morphology and energy dispersive X‐ray spectroscopy were used for characterization. Gallium‐grafted titanium was evaluated in comparison with silver‐grafted titanium for both in vivo and in vitro antibiofilm properties and for in vitro compatibility with human primary gingival fibroblasts. Surface‐modified materials showed: (i) homogeneous porous morphology, with pores of micrometric size; (ii) absence of cytotoxic effects; (iii) ability to support in vitro the adhesion and spreading of gingival fibroblasts; and (iv) antibiofilm properties. Although both silver and gallium exhibited in vitro strong antibacterial properties, in vivo gallium was significantly more effective than silver in reducing number and viability of biofilm bacteria colonies. Gallium‐based treatments represent promising titanium antibiofilm coatings to develop new bone implantable devices for oral, maxillofacial, and orthopedic applications. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 103A: 1176–1187, 2015.